Determination of naproxen using DBS: evaluation & pharmacokinetic comparison of human plasma versus human blood DBS. (August 2010) - Youhnovski, Nikolay; Michon, Joséée; Latour, Sylvain; Mess, Jean-Nicholas; Bergeron, Annik; Furtado, Milton; Rufiange, Marianne; Guibord, Pascal; Lefebvre, Marc; MacArthur, Robert B; Garofolo, Fabio
Background: Dried blood spots (DBS) sampling is a well-known technology for qualitative determination such as DNA analysis and screening of newborn metabolic disorders. The scientific community has recently expressed interest in applying the DBS technique for quantitative determination of drugs in biological fluid.Results: Two new bioanalytical assays were developed and validated for the determination of naproxen in human plasma and in DBS samples using liquid chromatography coupled with tandem MS. Furthermore, plasma and DBS clinical samples were collected from four subjects enrolled as part of a bioequivalence study. Concentration data for plasma and DBS samples were determined and pharmacokinetic (PK) profiles in plasma and in DBS samples were compared.Conclusions: A strong correlation between PK data obtained by the DBS and conventional plasma method was observed, which makes DBS a valuable technique for further naproxen bioavailability and PK investigations and studies.